Ethics training of medical students: the gap between the formal curriculum and the hidden curriculum - Suárez Obando, Fernando; Díaz Amado, Eduardo (Acta Bioethica, 2007)
To take right decisions in medicine from an ethical-moral point of view is a complex matter and to learn to do it must constitute one of the goals of medical training. A way to contribute to achieve this is to integrate a complete theoretical training in Medical Ethics and Bioethics with a true correlation in clinical practice experience. To take into account what students think and feel about the issue is a good reference to start. In the present paper the results on a workshop about the tipic, carried out whith medical students in advances training, are presented together with reflections raise in the workshop development.